Automation Smartlock for Implementing Smarthome Security Using Location Based Service - Sugihartono, Tri; Isnanto, Burham; Putra, Rendy Rian Chrisna; Sulaiman, Rahmat; Pradana, Harrizki Arie (Jurnal Telematika, 2019)
Currently, the development of technology is very rapid. Technology is used to assist humans in carrying out dailyactivities. One of the advances in technology is the developmentof tools that can control over long distances or remotely (the Internet of Things). IoT applications are for remote monitoringand smart home appliance controlling. We propose a mobile-based door security model. At present, there are many door security models, but in this study, we propose security at doors using Location Based Services (LBS). The door will automatically open and close. The user's location is based on the cell phone user’s location. If the user's location is outside the door area of the house, the door will be closed automatically. Instead, the door will open if the user has entered the house. With the security door model using LBS, the house will be secured. The door will automatically be locked when the owner is outside the house within a radius of 1 meter. With the application of Internet of Things (IoT) technology, residents will feel safe without worrying when traveling. The IoT technology used in this study is ESP 8266, as a Wifi module and as an opening tool that can move smart lock, to open and lock the door. The results of this study are the accuracy of the performance of the smart door lock system with location-based service by 70%.Saat ini perkembangan teknologi sangat pesat. Teknologi digunakan untuk membantu manusia dalam menjalankan aktivitas sehari-hari. Salah satu kemajuan dalam teknologi adalah pengembangan alat yang dapat mengontrol dalam jarak jauh (Internet of Things). Banyak aplikasi IoT adalah untuk memantau jarak jauh dan mengendalikan peralatan rumah tangga (smart home appliance). Kami mengusulkan model keamanan pintu berbasis mobile. Saat ini, ada banyak model keamanan pintu, tetapi dalam penelitian ini, kami mengusulkan keamanan di pintu menggunakan Layanan Berbasis Lokasi (LBS). Pintu akan secara otomatis membuka dan menutup. Lokasi pengguna berdasarkan yang diperoleh dari pengguna ponsel. Jika lokasi pengguna berada di luar area pintu rumah, pintu akan ditutup secara otomatis. Sebaliknya, pintu akan terbuka jika pengguna sudah masuk rumah. Dengan model keamanan pintu menggunakan LBS, rumah akan diamankan. Pintu akan otomatis terkunci ketika pemiliknya berada di luar rumah dalam radius 1 meter. Dengan penerapan teknologi Internet of Things (IoT) ini, penghuni rumah akan merasa aman tanpa khawatir jika bepergian. Teknologi IoT yang digunakan dalam penelitian ini adalah ESP 8266, sebagai modul wifi dan sebagai alat pembuka yang bisa menggerakkan smartlock, untuk membuka dan mengunci pintu. Hasil dari penelitian ini adalah akurasi kinerja aplikasi smartlock dengan location-based service sebesar 70%.